2020
DOI: 10.3390/nano10030424
|View full text |Cite
|
Sign up to set email alerts
|

MIL-88A Metal-Organic Framework as a Stable Sulfur-Host Cathode for Long-Cycle Li-S Batteries

Abstract: Lithium-sulfur (Li-S) batteries have received enormous interest as a promising energy storage system to compete against limited, non-renewable, energy sources due to their high energy density, sustainability, and low cost. Among the main challenges of this technology, researchers are concentrating on reducing the well-known "shuttle effect" that generates the loss and corrosion of the active material during cycling. To tackle this issue, metal-organic frameworks (MOF) are considered excellent sulfur host mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…In addition, the initial discharge specific capacities of the S@NUS-6, S@UiO-66(Hf) and S@CB electrodes were 972.2 mAh g À1 ,8 96.2 mAh g À1 and 830.2 mAh g À1 at 1C,r espectively,w hich is highert han other materials S@MOFse lectrode materials. [37][38][39] After 300 cycles, the capacity decay per cycle of S@NUS-6, S@UiO-66(Hf) and S@CB composite electrodes were 0.122 %, 0.157 %a nd 0.177 %, respectively ( Figure S5).…”
mentioning
confidence: 99%
“…In addition, the initial discharge specific capacities of the S@NUS-6, S@UiO-66(Hf) and S@CB electrodes were 972.2 mAh g À1 ,8 96.2 mAh g À1 and 830.2 mAh g À1 at 1C,r espectively,w hich is highert han other materials S@MOFse lectrode materials. [37][38][39] After 300 cycles, the capacity decay per cycle of S@NUS-6, S@UiO-66(Hf) and S@CB composite electrodes were 0.122 %, 0.157 %a nd 0.177 %, respectively ( Figure S5).…”
mentioning
confidence: 99%
“…In addition, MOF synthesis is largely conducted in solvothermal or hydrothermal conditions, which usually requires a high temperature and pressure with long reaction time, as indicated by the examples above [195,196]. These severe reaction conditions are also known to consume a lot of energy and reduce the production rate (in general STYs are below 300 kg m −3 per day) [55,197,198]. In addition, in terms of green applications, a crucial pre-requisite in the real world is the ability to achieve the low-cost synthesis of high-quality MOF materials in large quantities with high efficiency [45,199,200].…”
Section: Discussionmentioning
confidence: 99%
“…To date, many effective methods have been proposed for the green and cheap synthesis of UiO MOFs. However, there are few reports on their large-scale production from kilogram (kg) scale to commercialization at the ton (t) scale [6,55]. Recently, Karadeniz et al [154] reported a green mechanochemical synthesis approach for the continuous production of a series of Zr-MOFs (UiO-66, UiO-66-NH 2 , MOF-801 and MOF-804) using a non-conventional zirconium dodecanuclear acetate cluster and a small amount of water as the liquid-assisted grinding (LAG) additive.…”
Section: Uio Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption behavior for Bromophenol Blue was estimated. Benítez et al [16] synthesized MIL-88A@S composites by fast ultrasonic-assisted probe technique. The structural and electrochemical properties of the MIL-88A@S composite were investigated.…”
Section: Introductionmentioning
confidence: 99%